The Military Factor in Central Asia - Gómez de Ágreda, Ángel (UNISCI Discussion Papers, 2012)
The geostrategic importance of Central Asia, as it is located in the very heart of the continent, adds to its relevance as a provider and a route for significant energy resources which feed some of the most important emergent economies of the XXIst Century. The Armed Forces of the republics – the so called “stans” – deserve little consideration in the general context of the region. Their Armies, for the most part obsolete and inherited from the Soviets, are more focused on internal than external matters. The International Organizations in which they take part – be it the Community of Independent States, the Collective Security Treaty Organization or the Shanghai Cooperation Organization – are the most meaningful link in a region which is mostly dependent on its powerful neighbours.